Niftaveyh ve el-Maksûr ve'l-Memdûd adlı eseri - Buhan, Yusuf (My University, 2022)
Arap dili alanında önemli dil âlimlerinin yetişmesinde büyük bir rol oynayan Bağdat, III/ IX. ve IV/ X. yüzyıllarda öne çıkan ilim merkezlerinden birisi olmuştur. Ebû Abdillâh Niftaveyh de (ö. 323/ 935) Bağdat’ta bu asırlarda yaşamış önemli dil bilginlerinden biridir. Lügat, nahiv, şiir ve ahbâr ilimlerinin yanı sıra kelam, hadis, tefsir gibi diğer başka İslâmî ilimlerle de iştigal etmiştir. Ancak daha ziyade nahivci ve lügatçi kimliğiyle temayüz etmiştir. Çok yönlü bir âlim portresine sahip olan Niftaveyh, birçok alanda eser telif etmiş ve görüş bildirmiştir. Ne var ki eserlerinin çoğu günümüze ulaşmamıştır. Günümüze ulaşan iki eserinden biri, maksûr ve memdûd kelimelerin i‘râb, ikil-çoğul halleri, çeşitli çekimleri vb. durumlarını ele aldığı el-Maksûr ve’l-memdûd adlı eseridir. Tezde öncelikle Niftaveyh’in yaşadığı dönemin siyâsî, sosyal ve ilmî açıdan durumuna kısaca değinilmiştir. Hayatı hakkında bilgi verilmiş ve ders aldığı hocalar ve öğrencileri ele alınmıştır. Zira dönemin havası gereği hoca-talebe ilişkisi büyük bir önemi haizdir. Arap dilinin yanısıra diğer İslâmî ilimlerdeki birikimine değinilmiştir. İştikak ve dilin kökenine dair görüşlerine yer verildikten sonra maksûr ve memdûd literatürüne dair verilmiştir. Özel olarak ise Niftaveyh’in eseri maksûr ve memdûd geleneği açısından değerlendirilmiştir. Kelimelerin Arapça’daki kullanımları ve niteliklerinin ele alınması dilin anlaşılmasına katkı sağlamıştır. Zira bu tür kelimelerin Arap dilinde önemli bir yer tuttuğu söylenebilir. Bu çalışmada Niftaveyh’in ilmî hayatı ve kişiliğinin ortaya konulması hedeflenmiştir. Ayrıca genel olarak maksûr ve memdûd kelimeleri derleyen eserlerin nitelikleri özel olarak da Niftaveyh’in eserinin incelenmesi çalışmanın amaçları arasındadır. Çalışmanın sınırları gereği sadece öne çıkan maksûr-memdûd türü eserlere dair kısaca bilgi verilmiş ve Niftaveyh’in eseri detaylı bir şekilde incelenmiştir.

Baghdad, which played a major role in the training of important language scholars in the field of Arabic language, III/ IX. and IV/ X. It has been one of the prominent science centers for centuries. Abu Abdillâh Niftaveyh (d. 323/ 935) is one of the important linguists who lived in Baghdad during these centuries. He was engaged in other Islamic sciences such as theology, hadith, tafsir, as well as lexicon, syntax, poetry and ahbar sciences. However, he mostly distinguished himself as a nahivist and a lexicographer. Niftaveyh, who has a versatile scholar portrait, has written works and expressed opinions in many fields. However, most of his works have not survived. One of his two works surviving today is i'râb, dual-plural forms, various conjugations, etc. of the words maqsûr and mamdûd. It is his work called al-Maqsûr ve'l-mamdûd, in which he deals with the situations of In the thesis, first of all, the political, social and scientific situation of the period in which Niftaveyh lived is briefly mentioned. Information about his life was given and the teachers and students he took lessons from were discussed. Because, due to the atmosphere of the period, the teacher-student relationship is of great importance. In addition to the Arabic language, his accumulation in other Islamic sciences is mentioned. After giving place to his views on the origin and origin of language, general information about the literature of maqsûr and memdûd is given. In particular, Niftaveyh's work has been evaluated in terms of maqsûr and mamdûd tradition. Addressing the use and qualities of words in Arabic contributed to the understanding of the language. It can be said that such words have an important place in the Arabic language. In this study, it is aimed to reveal the scientific life and personality of Niftaveyh. In addition, it is among the aims of the study to examine the characteristics of the works that compile the words maqsûr and mamdûd in general, and the work of Niftaveyh in particular. Due to the limitations of the study, only brief information about the prominent maqsûr-memdûd works was given and Niftaveyh's work was examined in detail.
Keywords: Arabic Language; Arap Dili; Baghdad; Bağdat; Islam; İslam; Lügat; Maksûr; Mamdūd; Maqsūr; Memdûd; Niftaveyh; Niftaweyh